A serological study and risk factors associated with Akabane virus infection in cattle in Egypt - Selim, Abdelfattah; Marzok, Mohamed; Gattan, Hattan S.; Hereba, Abdelrahman M. (Scientific reports, 2025)
Akabane virus (AKAV) is an arbovirus belonging to the genus Orthobunyavirus within the family Peribunyaviridae , order Elliovirales 1 , capable of infecting ruminants such as cattle, sheep, and goats. This arthropod-borne virus is transmitted by mosquitoes or midges and has been recognized as a contributor to outbreaks of reproductive disorders. This study investigates the seroprevalence of AKAV infection in cattle across various regions in Egypt, along with an analysis of potential risk factors contributing to the infection. Serum samples from 540 cattle were collected randomly from four governorates and tested using a commercial competitive ELISA kit. The seroprevalence of AKAV infection was found to be 24.4%. Univariable statistical analysis indicated that factors such as locality, age, sex, breed, season, and history of abortion ( p < 0.05) were significantly associated with the infection, while herd size did not show a significant association ( p > 0.05). In addition, the multivariable logistic regression analysis indicated that the likelihood of AKAV infection was significantly higher in Alexandria (OR = 2.9, P = 0.001), in cattle over 5 years of age (OR = 3.7, P = 0.002), among females (OR = 2.7, P = 0.034), in Holstein breeds (OR = 2.1, P = 0.003), during the winter season (OR = 3.7, P < 0.0001), and in cattle with a history of abortion (OR = 2.5, P < 0.0001). These findings emphasize the need for ongoing monitoring of the disease in ruminants to accurately assess its burden and raise awareness. Such efforts will promote early detection and support the development of effective control measures for the disease in this region.